Determinants of organizational citizenship behavior: The case of manufacturing operators in manufacturing plant - Karu Selvamani, Karuppiah (2018)
Retaining employees in the organization is very crucial, especially to those organizations that require large pool of employees like manufacturing plant where 85% of their workforce are manufacturing operators. Retaining the lower level employees like manufacturing operators is very challenging as the employees leave the organization at any time due to various external and internal factors. There are not much focus and attention given on the importance of organizational citizenship behavior towards manufacturing operators. Thus, it is important to understand the factors that will influence in reaching organizational citizenship behavior among the manufacturing operators. The main objective of this study is to analyze the relationship between job satisfaction, trust in supervisor, organizational commitment, organization justice with the organizational citizenship behavior among the manufacturing operators in manufacturing organization. Data was collected by using the questionnaire that has been distributed to 226 respondents and as the respondents are within same organization, all the 226 questionnaire have been successfully collected for data analysis. Findings of the research revealed that all the four variables, job satisfaction, trust in supervisor, organizational commitment and organizational justice having significant relationship with the organizational citizenship behavior. The recommendation for the related stakeholders and future research were also discussed.